2020
DOI: 10.1002/jcp.30245
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal cancer prompted adipose tissue browning and cancer cachexia through transferring exosomal miR‐146b‐5p

Abstract: Cancer cachexia is a complex syndrome that is associated with thermogenic gene regulation. Currently, although some studies have reported the link between exosomes and cancer cachexia in a few types of cancer, the underlying mechanisms remain poorly understood. In this study, we tried to identify whether exosomes derived from colorectal cancer could affect lipolysis in vitro and in vivo. Here, we collected the tissue samples from 48 patients with colorectal cancer (47.91% females and mean age 55 ± 8.20) and 48… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 33 publications
0
29
0
Order By: Relevance
“…We also provided a comprehensive description of HOXC10 expression regulation. Specifically, HOXC10 expression is regulated by several epigenetic processes, including DNA ( 6 , 50 , 96 ) and histone ( 5 , 97 ) methylation, posttranscriptional miRNA ( 10 12 , 59 , 61 , 64 , 98 ) and lncRNA ( 9 , 99 ) modifications, and ubiquitin modifications ( 100 ).…”
Section: Hoxc10 Expression Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…We also provided a comprehensive description of HOXC10 expression regulation. Specifically, HOXC10 expression is regulated by several epigenetic processes, including DNA ( 6 , 50 , 96 ) and histone ( 5 , 97 ) methylation, posttranscriptional miRNA ( 10 12 , 59 , 61 , 64 , 98 ) and lncRNA ( 9 , 99 ) modifications, and ubiquitin modifications ( 100 ).…”
Section: Hoxc10 Expression Regulationmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are small noncoding RNAs that can degrade or suppress the translation of target mRNAs by base pairing with the 3’-untranslated region (3’UTR) ( 106 ). Several miRNAs, such as miR-129-5p ( 10 12 ), miR-222-3p ( 64 ), miR-146b-5p ( 98 ), miRNA-221 ( 61 ), and miRNA-136 ( 59 ), have been reported to play a key role in regulating HOXC10 expression. These miRNAs directly target the 3’UTR of HOXC10 to inhibit HOXC10 expression.…”
Section: Hoxc10 Expression Regulationmentioning
confidence: 99%
“…Similarly, structural and functional changes of white adipose tissue were observed in cachectic patients. This browning of adipose tissue may be linked to the effect of miR-146b-5p carried in exosomes [165]. This insidious syndrome dramatically impacts the quality of the remainder of the patient's life, but is also associated with poor responses to therapy and decreased survival [166].…”
Section: Effect Of Cancer Cell-derived Exosomes (Caexos) On the Funct...mentioning
confidence: 99%
“…Beside low food intake, adipose tissue dysfunction is a major player in cancer cachexia, during which white adipose tissue (WAT) is undergoing a browning process marked by increased lipid mobilization and energy expenditure [ 134 ]. Exosomal miR-146-5p derived from CRC cells could induce WAT browning and lipolysis, through repression of homeodomain-containing gene C10 (HOXC10), illustrating the importance of cell crosstalk in the tumor microenvironment [ 135 ]. Interestingly, in a pre-clinical model of CRC, it was shown that chemotherapy treatment decreased the size of adipocytes and also the expression of proteins involved in ATP production, β-oxidation and lipogenesis [ 136 ].…”
Section: Lipid Metabolism In the Tumor Microenvironmentmentioning
confidence: 99%